Cell-free regenerative medicine: identifying the best source of mesenchymal stem cells for skin therapy in Systemic Sclerosis - Napolitano, Filomena; Giudice, Valentina; D’Esposito, Vittoria; Prevete, Nella; Scala, Pasqualina; de Paulis, Amato; Selleri, Carmine; Formisano, Pietro; Rossi, Francesca Wanda; Montuori, Nunzia (Frontiers in Cell and Developmental Biology, 2025)
IntroductionSystemic Sclerosis (SSc) is a rare chronic systemic autoimmune disease characterized by fibrosis of the skin and internal organs and vasculopathy. Raynaud’s phenomenon is typically the earliest clinical manifestation accompanied by skin inflammation, finger ulcers, and organ manifestations, including pulmonary fibrosis. There is an urgent need for the development of effective targeted therapeutic intervention for SSc patients. A greater focus has been placed on bioactive factors secreted by Mesenchymal Stem Cells (MSCs), with immunomodulatory and regenerative potentials. Current data report a different secretion profile of MSCs, depending on the tissue of origin. Understanding of the secretion profile of different MSCs is necessary to identify the most efficient and useful source for SSc treatment.MethodsWe analyzed the content of MSC-conditioned media (MSC-CM) obtained from MSCs isolated from adipose tissue (AT), bone marrow (BM), Wharton’s jelly (WJ), and cord blood (CB) by ELISA method, and their effects on the wound healing process by fibroblast proliferation, migration, and ECM deposition assays, to compare regenerative potential of different MSC populations.ResultsWJ-MSC-conditioned medium (CM) and BM-MSC-CM show a greater regenerative profile, compared to CB-MSC-CM and AT-MSC-CM, due to the abundance of growth factors and immunomodulatory cytokines and the effects on fibroblast functions. In SSc fibroblasts, WJ-MSC-CM significantly promotes fibroblast-mediated wound healing processes and VEGF expression, compared to BM-MSC-CM.DiscussionOur data indicate that WJ-MSC-CM could be considered an appealing strategy to both topical and systemic administrations in SSc patients.